Determinants of factors that influence unethical advertising: A study of UUM'S management postgraduate students - Shariza, Semi (2016)
Nowadays, advertising industry in worldwide is experiencing fast and extraordinary changes. Commonly advertising are known to inform, persuade, and remind consumers but sometime prospect consumer’s about the existence of certain product or services in the certain market. Unfortunately, advertising has become as a target to criticism for decades. Advertising can be as advantages and not to forget the harm to the company who sponsor an advertising or citizens. Many disadvantages causes by advertising such as economic harms, cultural harms, moral and religious harms, and political harms if advertiser make mistake in the process to develop advertising. Thus, the aim of the study to examine the factors that influence advertising become unethical according consumer perspective. In this research Msc Management student in University Utara Malaysia are chooses to become as respondent. The total of 246 questionnaires were distributed to Master Science Management students which are consisting of Malaysia and Internationals and it takes around two week to get back all the questionnaires that have been distributed. However, out of 246 questionnaires that have been distributed, only 155 questionnaires can be analyzed. The outcome of the study indicates that 75.9 percent of the Msc Management student’s selection factor choose unethical advertising can be explained by the variable which are lack of truthfulness and honesty, offensive and surrogate advertising. Furthermore out of the three independent variables, the variables, specifically offensive advertising and surrogate advertising are found significant to be factor that have relationship why advertising become unethical while, the lack of truthfulness variable is not significant to factor that have relationship why advertising become unethical.